Design and Performance Analysis of Linear Array Microstrip Antennas with Mitered-Bends Feeding Network for X-Band Radar Applications - Bidadariana Yunia Utami Putri; Eka Setia Nugraha; Anantia Prakasa; Subroto Fajar Siddiq (National Research and Innovation Agency, 2020)
To accurately detect objects, the radar antenna must have a high gain for the desired range. The antenna uses an array method to increase the gain. It has a unidirectional radiation pattern to meet the X-band radar implementation as a ship navigation tool. The X-band radar works at high frequencies. Thus, it will be more sensitive in detecting small particles, including rain particles. The use of a mitered-bends feeding network method by cutting the 90-degree curve is to maximize the power transmitted to reduce losses. This method spreads the bandwidth of the antenna. The antenna is designed and fabricated into a linear array of 8 elements, using the R04003C Rogers substrate with a microstrip line supply. This study limits up to 8 elements of radiation, followed by the addition of a method to expand the bandwidth of antennas. Considering material limitation and duration of antenna design. The final antenna dimensions are 142.40 mm × 42.8 mm. The measuring results show fc = 9.496 GHz, S11 = -32.64 dB, VSWR 1.05, bandwidth = 41.9 MHz (9.5159 GHz - 9.4740 GHz), and gain 8.8 dB as well as a linear polarized antenna with unidirectional pattern direction. The radar antenna tends to have a narrow beamwidth and high gain.